Heterogeneity of the Glyoxylate-Condensing Enzymes - Wegener, Warner S. (1965)
Wegener, Warner S. (Albert Einstein Medical Center, Philadelphia, Pa.), Henry C. Reeves, and Samuel J. Ajl. Heterogeneity of the glyoxylate-condensing enzymes. J. Bacteriol. 90:594–598. 1965.—Evidence is presented that the enzymatic condensations of glyoxylate with acetyl-CoA (malate synthase), propionyl-CoA (α-hydroxyglutarate synthase), butyryl-CoA (β-ethylmalate synthase), and valeryl-CoA (β-n-propylmalate synthase) are catalyzed by different enzymes. The possibility that these activities resulted from a single enzyme possessing a broad fatty acid acyl-CoA substrate specificity was ruled out. The latter was suggested by the fact that cells grown on a number of short-chain fatty acids exhibited all the above activities. The conclusion that these reactions are catalyzed by different enzymes is based on the following considerations: (i) the enzymes can be differentially inactivated by heat; (ii) under various growth conditions, where all the condensing enzymes are present, their respective activities do not show a constant ratio, as would be expected if they were catalyzed by a single enzyme; and (iii) under appropriate growth conditions, one or more of these enzymes has been shown to be present to the exclusion of others.